ANALISIS BIAYA ENERGI PADA BEBERAPA INDUSTRI KAYU LAPIS DI KALIMANTAN TIMUR. Analysis of Energy Cost at Several Plywood Factories in East Kalimantan - SYLVIANI SYLVIANI (Pusat Penelitian dan Pengembangan Hasil Hutan, 1993)
Several plywood factories in East Kalimantan showed that they use wood waste and diesel fuel for energy sources for power generation and electricity. Five plywood factories surveyed produced wood waste with average of 112,590 cubic m in 1991 and its utilization for energy source amounted to 59,601 cubic m on average, while average consumed diesel fuel was 10,000 litres / month .This study showed that operational cost of power generation on average was Rp 290,394,316 per year in which the cost for fuel was Rp 204,122,020 ( 70 % from total operational cost) while the cost of fuel in the factories that used wood waste was Rp 26,535,863.Besides factories that used wood produced electricilymore, so that average cost / kwh was smaller namely Rp 71.50 / kwh compared with those used diesel, namely Rp 307 / kwh.